2012
DOI: 10.1038/nrurol.2011.225
|View full text |Cite
|
Sign up to set email alerts
|

XMRV and prostate cancer—a 'final' perspective

Abstract: XMRV was first described in 2006, when it was identified in samples isolated from prostate cancer tissues. However, studies have since shown that XMRV arose in the laboratory and was formed by genetic recombination between two viral genomes carried in the germline DNA of mice used during serial transplantation of the CWR22 prostate cancer xenograft. These new findings strongly imply that XMRV does not circulate in humans, but is only present in the laboratory. Thus, there is no reason to believe that it has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In contrast, in other studies have been found very low or no XMRV prevalence in prostate cancers in Europe (Germany, and the Netherlands) and USA using only RT-PCR (Fischer et al, 2008;Hohn et al, 2009;Aloia et al, 2010;Silverman et al, 2010;Sakuma et al, 2011;Sfanos, 2011;Stieler et al, 2011). Moreover other findings imply that XMRV does not present in humans, and is only seen in the laboratory contamination (Sfanos et al, 2012). Thus, the role of XMRV in human pathogenesis is controversial (Switzer et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, in other studies have been found very low or no XMRV prevalence in prostate cancers in Europe (Germany, and the Netherlands) and USA using only RT-PCR (Fischer et al, 2008;Hohn et al, 2009;Aloia et al, 2010;Silverman et al, 2010;Sakuma et al, 2011;Sfanos, 2011;Stieler et al, 2011). Moreover other findings imply that XMRV does not present in humans, and is only seen in the laboratory contamination (Sfanos et al, 2012). Thus, the role of XMRV in human pathogenesis is controversial (Switzer et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Several follow-up studies, however, did not detect XMRV in PCa patient samples (Fischer et al, 2008; Sfanos et al, 2008; Hohn et al, 2009; Aloia et al, 2010; Sakuma et al, 2011; Switzer et al, 2011). In addition, studies conducted in 2009 (Schlaberg et al, 2009) and 2010 (Arnold et al, 2010; Danielson et al, 2010) supporting the presence of XMRV in PCa had apparent contradictions to the original report as well as to each other, including discrepancies in the presence of virus in tumor versus benign tissues and discordance in cellular localization (reviewed in Sfanos et al, 2012). Despite this, the possibility of a viral cause to PCa proved to be an exciting prospect, prompting follow-up studies in PCa as well as other diseases.…”
Section: The Story Of Xmrvmentioning
confidence: 99%
“…These emerging concerns led to intensive discussions and investigations of XMRV, including molecular and biological characterization of the virus and the development of assays, standards, and nonhuman primate (NHP) models for further studies of human infection and disease association. The results of several studies evaluating XMRV infection in humans indicated that the results of the original reports were due to sample and/or laboratory contaminations (12)(13)(14)(15)(16)(17)(18)(19). Furthermore, XMRV was found at high titers in the 22Rv1 human prostate cancer cell line (20) and was recently shown to have most likely originated from recombination between two different endogenous murine retrovirus sequences during derivation of the 22Rv1 human prostate cancer cell line by serial passage of a human prostate tumor xenograft in nude mice (21,22).…”
mentioning
confidence: 99%